Peran Pesantren Syamsul Ulum Dalam Memperjuangkan Kemerdekaan Indonesia Di Sukabumi (1945-1946) - Nisa Fadlila Rahma; Mahbub Hefdzil Akbar (Priangan: Journal of Islamic Sundanese Culture, 2023)
This research was conducted to find out what roles the Syamsul Ulum farmers had played in fighting for Indonesian independence in Sukabumi. The method used in this study is the historical method, in which the author carries out several stages, namely heuristics, criticism, interpretation, historiography. The result of this research is to find the facts that when the Syamsul Ulum Islamic Boarding School participated in the battle against the allies that took place in Sukabumi, kh. Ahmad Sanusi as the founder of the pesantren founded several classes whose members were his students at that time. When the battle occurred, this class joined TKR to fight against the allies.